Culture, work motivation and competence influences on the performance of PUD Tohaga Market employees - Isbat, Isbat; Sasongko, Hendro; Pranowo, Agus Setyo; Hamzah, Hamzah (Indonesian Journal of Multidisciplinary Science, 2024)
The aim of this research is to determine and analyze the influence of work culture, competence and motivation on employee performance. The object of research is employees at the Regional Public Company (PUD), hereinafter abbreviated to PUD Pasar Tohaga, Bogor Regency. In this research, quantitative descriptive methods were used. The sampling technique used total sampling with a sample size of 30 people, using factor analysis, namely multiple linear regression. The research results show that: (1) partially organizational work culture variables influence employee performance in public companies in the Tohaga market area; (2) partially the competency variable influences employee performance in public companies in the Tohaga market area; (3) partially motivational variables influence employee performance in public companies in the Tohaga market area; (4) simultaneously there is a positive and significant influence between the variables of organizational culture, competence and motivation on employee performance in public companies in the Tohaga market area.